Combination of etoricoxib and low-pressure pneumoperitoneum versus standard treatment for the management of pain after laparoscopic cholecystectomy: a randomized controlled trial - Wasana Ko-iam (2018)
© 2016, Springer Science+Business Media New York. Background and objectives: Postoperative pain is one of the significant problems in laparoscopic surgery, especially during the first 6–12 h. This randomized controlled trial aimed to investigate the effect of combined preemptive etoricoxib 120 mg and low-pressure pneumoperitoneum for the management of pain after laparoscopic cholecystectomy (LC). Patients and methods: One hundred and twenty patients aged 18–75 with American Society of Anesthesiologists class I–II who were candidates for elective LC were recruited into the study. The patients were randomly divided into two groups, by ‘block of four’ randomization. The treatment group received preemptive etoricoxib 120 mg and intraabdominal pressure of 7 mmHg, and the control group received placebo and intraabdominal pressure of 14 mmHg. The postoperative pain score at rest was recorded utilizing a numeric rating scale at 1, 2, 6, 10, 14, 18, 22, and 24 h. Pain on movement/ambulation (cough) was also recorded at 6, 10, 14, 18, 22, and 24 h. Results: There were no significant differences in the baseline characteristics of the two groups. The pain scores of the treatment versus control group of abdominal pain and incisional pain were significant on movement. Abdominal pain scores of the treatment group were decreased 0.98 when compared with the control group (p = 0.017), and incisional pain scores were also decreased 0.99 (p = 0.001). The incidences of postoperative shoulder/back pain were statistically significant: 41.8 % vs. 66.7 % in the treatment and control group, respectively (p = 0.009). The postoperative hospital stay in the treatment group and control group was: 1 day = 96.4 and 75.0 %, >1 day = 3.6 and 25.0 %, respectively (p = 0.001). Conclusions: A combination of preemptive etoricoxib and low-pressure pneumoperitoneum had significant effects in decreasing overall pain and the incidence of shoulder/back pain after LC and also shortened the hospital stay. Clinical trials registration number: TCTR20140213001.